Saturday is Dadurday - Pulver, Robin (Walker Books for Young Readers, 2013)
"For Mimi, the best day of the week is always Saturday, the day she gets to spend with just her Dad. But when Dad's work takes him away from Mimi one Saturday, 'Dadurday' is ruined. Can Mimi find a way to save 'Dadurday' and still make it special for her and her Dad?"--